GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 107028 species occurrences available in GBIF matching the query: TaxonKey: Meles meles (Linnaeus, 1758) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 107028 records from 179 constituent datasets: 1 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 95 records from Mid Ulster Hare Surveys 2012-2015. 6 records from MVZ Mammal Collection (Arctos). 12 records from Faunal Inventory of Morysin Nature Reserve. 3 records from PlutoF platform observations. 406 records from BioGIS - Mammals - INPA database. 4 records from KUBI Mammalogy Collection. 2 records from Local BioBlitz Challenge 2013. 2612 records from Inventario Español de Especies Terrestres (MAGRAMA). 33 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 4091 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 19 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 156 records from BioFokus. 17 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 2 records from UAM Mammal Collection (Arctos). 932 records from Artdata. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1 records from Cowan Tetrapod Collection - Mammals. 8 records from Field Museum of Natural History (Zoology) Mammal Collection. 22 records from Lund Museum of Zoology (MZLU). 419 records from Données ONF Faune-Flore-Fonge. 1063 records from Road Kill Survey. 197 records from Norwegian Biodiversity Information Centre - Other datasets. 5 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 97 records from iNaturalist Research-grade Observations. 3 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 77 records from Mammals housed at MHNG, Geneva. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 84 records from BioGIS - Mammals - SPNI. 54 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 38 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from FNL e.V.. 1 records from Feriendorf Ober-Seemen. 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 1 records from Sudeniederung (Amt Neuhaus). 2561 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 447 records from The Mammal Society - National Mammal Atlas Project, online recording. 412 records from naturgucker. 25 records from Vertebrats d'Andorra. 1 records from CAS Mammalogy (MAM). 6 records from UMMZ Mammal Collection. 15 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 5 records from National Trust - Hatfield Forest species data held by The National Trust.. 64 records from BioGIS - Hamaarag. 1 records from Eschlberg Thalhausen. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 22 records from Mammal Collection. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from "Schule am Inselsee" Güstrow. 2 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 2 records from EDIT - ATBI in Spreewald (Germany). 11 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 36 records from Ireland's BioBlitz. 5 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 4 records from Akita Prefectural Museum＋Mammalians Specimens of Akita Prefectural Museum. 7 records from Ibaraki Nature Museum, Mammals collection. 1 records from UWBM Mammalogy Collection. 26 records from Paleobiology Database. 1 records from Mammals Specimens. 12806 records from Inventaire National du Patrimoine Naturel : Enquête carnivores. 585 records from Israel Nature and Parks Authority. 1250 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 1 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 1 records from Überall ist Wunderland. 1 records from Am Moosangerweg. 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Gemeinde Sursee. 1 records from Angelberger Forst - Klassen 3 a und 3 b. 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Neckartalsüdhang (Horb). 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from BUND - Dassower See (Lübeck/Dassow). 1 records from Unser Schulgelände. 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Quarrendorfer Landschaftsschutzgebiet. 1 records from Faberpark (Nürnberg/Stein). 1 records from Wismar Bucht coast-watching. 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 3 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 3 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 2 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 1 records from Occurrence of mammalia relicts at site Malerfels_I. 4 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 1 records from Occurrence of mammalia relicts at site Bocksteingrotte/Lonetal. 2 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 1 records from Occurrence of mammalia relicts at site la Grotte du Thai. 1 records from Occurrence of mammalia relicts at site Tornewton Cave. 2 records from Occurrence of mammalia relicts at site Rislisberghöhle. 1 records from Occurrence of mammalia relicts at site Stellmoor. 9 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1 records from Occurrence of mammalia relicts at site Meiendorf. 1 records from Occurrence of mammalia relicts at site Koziarna Cave. 1 records from Occurrence of mammalia relicts at site Trou du Renard. 1 records from Occurrence of mammalia relicts at site Sveduv stul. 1 records from Occurrence of mammalia relicts at site Geißenklösterle. 4 records from Occurrence of mammalia relicts at site Veternica. 1 records from Occurrence of mammalia relicts at site Sandalja II. 3 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 1 records from Occurrence of mammalia relicts at site Subalyuk. 1 records from Occurrence of mammalia relicts at site Erd. 1 records from Occurrence of mammalia relicts at site Istalloskö. 1 records from Occurrence of mammalia relicts at site Pilisszanto 1. 2 records from Occurrence of mammalia relicts at site Bedburg-Königshoven. 1 records from Occurrence of mammalia relicts at site Felsställe. 1 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 2 records from Occurrence of mammalia relicts at site Bettelküche. 1 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 9 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 1 records from Occurrence of mammalia relicts at site Bärenfelsgrotte. 1 records from Occurrence of mammalia relicts at site Steinheim an der Murr. 1 records from Occurrence of mammalia relicts at site Barrington. 1 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 3 records from Occurrence of mammalia relicts at site Ettingen. 1 records from Occurrence of mammalia relicts at site la Grotte des Fees. 1 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 1 records from Occurrence of mammalia relicts at site Nietoperzowa. 1 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 5 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 3 records from Occurrence of mammalia relicts at site l´Abri du Morin. 1 records from Occurrence of mammalia relicts at site Roc de Combe. 4 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 1 records from Occurrence of mammalia relicts at site Zemst Bos van A. 1 records from Occurrence of mammalia relicts at site Goyet Cave 3. 2 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 1 records from Occurrence of mammalia relicts at site Klithi. 1 records from Occurrence of mammalia relicts at site Risovaca. 1 records from Occurrence of mammalia relicts at site Predmosti. 1 records from Occurrence of mammalia relicts at site Smolucka Pecina. 3 records from Occurrence of mammalia relicts at site Pestera Cioarei. 2 records from Occurrence of mammalia relicts at site Erdhöhle. 1 records from Occurrence of mammalia relicts at site Grotte Scladina. 2 records from Occurrence of mammalia relicts at site Igrita Cave. 1 records from Occurrence of mammalia relicts at site Icoana. 2 records from Occurrence of mammalia relicts at site Fuchsenloch. 1 records from Occurrence of mammalia relicts at site Felslindlhöhle. 1 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 2 records from Occurrence of mammalia relicts at site Felsställe. 1 records from Freiburger Netzwerk Artenvielfalt. 149 records from DOF. 374 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 4 records from Gunma Museum of Natural History, Mammal Specimen. 318 records from Biological and palaeontological collection and observation data MNHNL. 28 records from DOF 2001-2006. 1 records from Mammal Specimens. 1 records from Wetland Inventory (NV). 11 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 2 records from National Trust - Sutton Hoo species data held by The National Trust.. 112 records from ArtenFinder. 8 records from BioGIS - Mammals - HUJ collections. 6 records from National Trust - Ickworth species data held by The National Trust.. 61861 records from Irish National Badger Sett Database. 1111 records from Norwegian Species Observation Service. 2 records from MSB Mammal Collection (Arctos). 8 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1526 records from Highland Biological Recording Group - HBRG Badger dataset. 1 records from Flora of County Cavan. 6884 records from Atlas of Mammals in Ireland 2010-2015. 4 records from Mammalogy Collection - Royal Ontario Museum. 500 records from Estonian Nature Observations Database. 107 records from Large mammals in Israel from camera traps. 2 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 419 records from Données ONF Faune-Flore-FOnge. 120 records from Hare Survey of Ireland 06/07 - Non Hare records. 13 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 31 records from National System of Protected Areas in Poland - Animals. 6 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 5 records from Anymals+plants - Citizen Science Data. 820 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 150 records from Data collected on scitizen science web portal www.ornitho.cat. 1 records from Collection Mammalogie - ZSRO. 3424 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 120 records from Hare Survey of Ireland 06/07. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences